Goldilocks and the three electricity prices: Are Irish prices just right? - Conor Devitt; Seán Diffney; John Fitz Gerald; Laura Malaguzzi Valeri; Aidan Tuohy (The Economic and Social Research Institute (ESRI), 2011)
In this paper we analyse the 2008 electricity price in the Irish All-Island Market. We test whether this price is 'efficient' by comparing it to the electricity price in Great Britain. This analysis suggests that around exteuro16 per MWh of the difference in wholesale prices between Ireland and Britain is due to differences in generating technology. The new wholesale electricity market for the island of Ireland appears to be working well - it is producing a wholesale price that approximates the long run marginal cost that would apply in a large liquid competitive market. In the British market the wholesale price appears to be below the long run marginal cost of producing electricity. Retail margins in Great Britain are high, especially for households. Only some of this margin compensates vertically integrated utilities for the low wholesale price. In the Republic of Ireland the retail margin was probably also higher than it should have been.
Keywords: 330